Physiological and productive characteristics of the banana 'Prata-Anã' subjected to different irrigation intervals and emitter heights - Gabriel Gustavo Alves Lage; José Alberto Alves de Souza; Carlos Elízio Cotrim; Sérgio Luiz Rodrigues Donato; Alessandro de Magalhães Arantes (Acta Scientiarum. Agronomy, 2020)
This study aimed to evaluate the productive characteristics, gas exchange and water use efficiency of the banana 'Prata-Anã' clone Gorutuba under different irrigation intervals associated with different emitter heights. Therefore, a field experiment was conducted in a 2 x 4 factorial scheme: two irrigation intervals (daily and every two days) and four emitter heights (50, 70, 90, and 110 cm) in a completely randomized design with four replicates. The irrigation depths applied by the microsprinkler irrigation system were calculated as a function of crop evapotranspiration. The gas exchanges were evaluated during the period of greatest climatic stress, and the productive characteristics were evaluated at harvest. The economic water use efficiency was determined indirectly by considering the production divided by the applied irrigation depth, which was the same in all the treatments. The instantaneous water use efficiency was estimated with an infrared gas analyzer in the critical climatic period. There was no interaction between the irrigation intervals and emitter heights. The two-day irrigation interval resulted in lower values of leaf temperature and photosynthetically active radiation incident on the leaves, resulting in a higher fruit weight and, consequently, higher yields and a higher water use efficiency. The highest fruit weights were obtained at heights of 70 and 90 cm.